Neurilemmoma of nose - Pradhan M Pagaro; Tushar Patil; Priyanka K Chaudhari; Archana Buch (Medical Journal of Dr. D.Y. Patil University, 2013)
Neurilemmomas are uncommon neoplasms. They are solitary encapsulated benign tumors usually occurring along the course of peripheral, cranial or sympathetic nerve. They are rarely malignant. Nasal and paranasalneurilemmomas are extremely rare and few cases have been reported. We report a case of neurilemmoma of nose because it is rare and it grossly appears similar to the benign mucous polyp of the nose. We report a 32-year-old male complaining of foreign body sensation in nose and difficulty in breathing. On examination it was clinically thought to be a mucous polyp, but on histopathological examination it was found to be neuroilemmoma.